Research assessment and openness - a multifaceted relationship (Pubmet, 2025)
Bianca Kramer will explore the multi-faceted relationship between research assessment and openness. Questions around openness shape the lenses through which we look at research assessment - considering both who and what we include in assessment of research and researchers, and how such assessments can be performed.